2020
DOI: 10.1111/jmft.12454
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting Stance and Mitigating Therapist Authority in Open Dialogue Meetings

Abstract: Open Dialogue is a collaborative systemic approach to working with families in crisis. A core feature is the creation of dialogue through the elicitation of a multiplicity of voices. Using conversation analysis, we studied 14 hr of Open Dialogue sessions. We found that therapists recurrently produced utterances containing “I’m wondering.” These utterances topicalized particular issues and invited stance positions from other participants while also allowing the therapist to mitigate their deontic authority and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…In this article, I will describe how this new perspective has shaped my thinking, practice, and approach to family therapy. I will therefore write in the first person to emphasise that these ideas reflect my own personal development and how they have changed the way that I view family therapy rather than focusing on the empirical findings of my research, which readers can find elsewhere (Ong, Barnes, & Buus, 2020a, 2020b, 2020c, 2021, 2021). I will briefly say a little about conversation analysis before moving on to some of the more specific ideas that have been interesting to me.…”
Section: Conversation Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In this article, I will describe how this new perspective has shaped my thinking, practice, and approach to family therapy. I will therefore write in the first person to emphasise that these ideas reflect my own personal development and how they have changed the way that I view family therapy rather than focusing on the empirical findings of my research, which readers can find elsewhere (Ong, Barnes, & Buus, 2020a, 2020b, 2020c, 2021, 2021). I will briefly say a little about conversation analysis before moving on to some of the more specific ideas that have been interesting to me.…”
Section: Conversation Analysismentioning
confidence: 99%
“…As noted by Heritage (2013, p. 290), ‘it is within these local sequences of talk, and only there, that these institutions are ultimately and accountably talked into being.’ People may, of course, resist these default positions. For example, parents may exert their authority to describe the relevant symptoms for their child and disagree with doctors’ treatment recommendations (Stivers, 2007) and therapists may downgrade their deontic authority (Ong, Barnes, & Buus, 2020c, 2021). But these examples are notable because they are departures from expectations (Potter, 1996).…”
Section: Conversation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…CA studies have identified that therapists can respond to client disagreements by retreating from their prior formulation to affiliate and strengthen the client's alternative position (Muntigl et al, 2013), or the therapist can maintain their position in either a convergent and supportive way or a divergent and unsupportive way, implying that either the therapist's or the client's understanding was in need of correction (Viklund et al, 2010;Weiste, 2015;Muntigl et al, 2013). More recent studies have shown how therapists work to downgrade both their deontic and epistemic authority in Structural Family Therapy and Open Dialogue sessions (Muntigl and Horvath, 2020;Ong et al, 2020cOng et al, , 2021. By downgrading their epistemic authority through phrases such as 'what I hear.…”
mentioning
confidence: 99%
“….' (Ong et al, 2021), therapists defer to the epistemic authority of their clients and promote reflection and elaboration. As a whole, these studies show how therapists balance introducing new ideas that may be beneficial to the client with having to maintain therapeutic engagement, social solidarity and respect for the epistemic authority of the client and family.…”
mentioning
confidence: 99%